2013
DOI: 10.1002/aur.1318
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Face and Non‐Face Stimuli in Autistic Spectrum Disorder

Abstract: The ability to remember faces is critical for the development of social competence. From childhood to adulthood, we acquire a high level of expertise in the recognition of facial images, and neural processes become dedicated to sustaining competence. Many people with autism spectrum disorder (ASD) have poor face recognition memory; changes in hairstyle or other non-facial features in an otherwise familiar person affect their recollection skills. The observation implies that they may not use the configuration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 61 publications
(76 reference statements)
1
11
0
Order By: Relevance
“…Not only is face memory responsive to treatment but may also be associated with concomitant changes in social competence. For example, other studies have demonstrated that better face memory has been associated with more reciprocal social play (Corbett et al 2014a) and fewer ASD symptoms (Arkush et al 2013). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only is face memory responsive to treatment but may also be associated with concomitant changes in social competence. For example, other studies have demonstrated that better face memory has been associated with more reciprocal social play (Corbett et al 2014a) and fewer ASD symptoms (Arkush et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, most individuals with ASD show significant difficulty in remembering facial information, especially following a delay (Weigelt et al 2012). Better face memory has been associated with more reciprocal social play in children (Corbett et al 2014a) and fewer characteristics of autism in adolescents with ASD (Arkush et al 2013; Eussen et al 2015). Thus, remembering facial information is an important marker of social skills and a target for treatment.…”
Section: Social Competence Frameworkmentioning
confidence: 99%
“…More is known about face memory, although the ASD group shows extensive heterogeneity. Adolescents with ASD exhibited reduced memory for faces but not houses on a “surprise” memory task (Arkush, Smith-Collins, Fiorentini, & Skuse, 2013). Performance of the teens with ASD across the face and object memory conditions was correlated, whereas it was not for the comparison group, suggesting that memory processing for faces may be domain general in ASD.…”
Section: Adolescence and Adulthoodmentioning
confidence: 99%
“…For instance, autism spectrum disorder is another neurodevelopmental disorder that is also characterized by severe social dysfunction. Relevant to this discussion, individuals with autism spectrum disorder show a performance pattern consistent with disrupted social preference [7981] as well as impairments on various social cognitive tasks [8284]. There is also longitudinal evidence linking social preference to social functioning in autism spectrum disorder; children with autism spectrum disorder who could better detect others’ gaze during early childhood (around 4 years old) later showed better social functioning in adulthood [85].…”
Section: Disrupted Social Preference Nmdar Hypofunction and Social mentioning
confidence: 99%